94.7k views
1 vote
YO!!!!!!WILL GIVE 100 POINTS!!!!!!!!!!!BRAIN!!!!!!!!!!!!

YO!!!!!!WILL GIVE 100 POINTS!!!!!!!!!!!BRAIN!!!!!!!!!!!!-example-1
User GetFuzzy
by
5.5k points

2 Answers

4 votes

Answer:

Following function:

f (x) = {(x + 2)²} × (x-4) × (x + 1)³

The roots are given by:

{(x + 2)²} × (x-4) × (x + 1)³ = 0

x + 2 = 0

x = -2

x-4 = 0

x = 4

x + 1 = 0

x = -1

Answer:

option A

Explanation:

User Fortboise
by
6.0k points
1 vote
For this case we have the following function:
f (x) = ((x + 2) ^ 2) * (x-4) * (x + 1) ^ 3
The roots are given by:
((x + 2) ^ 2) * (x-4) * (x + 1) ^ 3 = 0
x + 2 = 0
x = -2 (multiplicity 2)
x-4 = 0
x = 4 (multiplicity 1)
x + 1 = 0
x = -1 (multiplicity 3)
Answer:
option A
User Mariano L
by
5.7k points